The Influence of Academic Pressure, Academic Procrastination and Ability with Self Efficacy as a Moderating Variable on Student Academic Fraud Behavior - Murdiana Murdiana; Efendri Efendri; Zainul Kisman; Dwi Sunu Kanto (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This study aims to analyze the effect of academic pressure, academic procrastination, and ability with self-efficacy as a moderating variable on student academic cheating. The population used in this study were Trilogy University students. The sample was determined using a purposive sampling method. The data analysis technique uses Partial Least Square (PLS) with the SEM (Structural Equation Modeling) method or the Structural Equation Model with the PLS Warp program. The data source used is primary data obtained by distributing questionnaires. The results of this study indicate that academic pressure, academic procrastination, and ability to have a positive and significant effect on academic cheating and self-efficacy do not moderate the impact of the three independent variables above on academic cheating.